48 días hacia el trabajo que ama : preparándose para la nueva normalidad - Miller, Dan, 1937-; Miller, Dan, 1937- (Morgan James Publishing, 2019)
Guides people working in jobs they hate on how to make successful career decisions by creating a compass from their natural skills and abilities, personality traits, values, dreams, and passions, directing them to a more fulfilling vocation.